PENGARUH FIRM SIZE, PROFITABILITAS, CORPORATE GOVERNANCE DAN LEVERAGE TERHADAP TAX AVOIDANCE (Studi Pada Perusahaan Manufaktur Yang Terdaftar di Bursa Efek Indonesia Tahun 2015 - 2017) - Abrar Oemar (Jurnal Ekonomi dan Bisnis Kontemporer, 2019)
This study aims to analyze the factors that influence tax avoidance practices in cement sector manufacturing companies listed on the Indonesia Stock Exchange from 2015 to 2017. This study examines factors such as: Firm Size, Profitability, Audit Quality, Audit Committee, and Leverage as independent variables, while the dependent variable in this study is Tax Avoidance.The population in this study are cement sector companies listed on the Indonesia Stock Exchange from 2015 to 2017, while the samples in this study were determined by purposive sampling method so that the number of samples was 39 companies and the number of observations was 117 times. The type of data used is secondary data obtained from www.idx.co.id and sample company websites. The analysis method used is multiple regression analysis.The results of this study indicate that the Audit Committee and Leverage influence Tax Avoidance, while Firm Size, Profitability and Audit Quality have no effect on Tax AvoidanceKeywords: Tax Avoidance, Firm Size, Profitability, Audit Quality, Audit Committee, and Leverage.